Climate change and its awareness among paddy farmers in central province of sri lanka - Alahakoon, P.C.B.; Wanigasundera, W.A.D.P.; Pallawala, R. (University of Jaffna, 2012)
Global climate change (CC) is the severest threat that is faced by the contemporary world. It has been experienced that the negative impacts of the CC are recently increasing in Sri Lanka. Paddy sector is one of the most vulnerable sectors in the country, to the effects of CC. Central province, where small scale and mostly rain-fed paddy farming is practiced, is highly vulnerable to the natural disasters and other negative impacts of CC. This study was conducted to assess the status of CC using long term metrological data and the perceptions of paddy farming community on CC in Kandy district and to assess their awareness on CC and on adaptation to the CC impacts. Yatinuwara Divisional Secretariat Divisions (DSD) in the mid country wet zone and Kundasale DSD in the mid country intermediate zone were selected for the study. Using multistage sampling, 32 farmers were selected from 12 villages of each DSD for the social survey. Meteorological data for 33 years for the DSDs were collected from the Department of Agriculture, Sri Lanka. Both descriptive and inferential statistics were used in the analysis. Results showed that the mean annual rainfall and rainy days have been increased in both DSDs and the mean annual temperature has increased in Yatinuwara. Majority of the respondents in Kundasale (84%) and Yatinuwara (81%) believed that there is a climate change in the area. Perception analysis has shown that, Kundasale farmers had more correct perceptions on CC than that of Yatinuwara. The farmers’ knowledge on adaptation strategies to the CC, overall attitudes on CC were significantly higher than that of Yatinuwara. The level of education and income showed a significant positive relationship with the overall attitudes on CC. It is recommended to develop and implement strategies to communicate the past trends and the predictions of CC correctly to the farmers. Data from hundreds of rainfall stations available throughout the country would be useful here. Conducting training programs to increase awareness and changing attitudes of farmers on important adaptation strategies to the CC such as soil moisture conservation also recommended.